Personal care burden and emotional symptoms among young carers supporting family members with mental health problems - Norihito Oshima; Naohiro Okada; Ryo Morishima; Akiko Kanehara; Yusuke Takahashi; Akito Uno; Shunichi Sato; Eureka Kumagai; Kaori Usui; Sho Kanata; Kiyoto Kasai (Psychiatry and Clinical Neurosciences Reports, 2026)
Abstract Aim Although research on the prevalence and psychological difficulties of young carers has increased, little is known about how their difficulties differ according to the type of disability or illness of the care recipient. This study examined the association between the type of disability of care recipients and psychological difficulties among Japanese junior and senior high school students. Methods A total of 860 students participated in a self‐administered survey that included the Young Carers Scale–Japanese version (YCS‐J), the Multidimensional Assessment of Caring Activities Checklist for Young Carers (MACA‐YC18), and the Strengths and Difficulties Questionnaire (SDQ). Multiple regression analyses were conducted to identify which types of family members were cared for and which disability or disease categories were associated with perceived difficulties. Post hoc analyses were performed to examine patterns in MACA‑YC18 and SDQ scores among young carers supporting family members with mental health problems. Results The prevalence of young carers was 8.8% ( n = 76). Multiple regression analysis revealed that having a care recipient with a mental health problem was a significant predictor of higher total difficult scores on the SDQ (adjusted R 2 = 0.014, F [11, 844] = 2.119, p = 0.017). Young carers supporting family members with mental health problems were significantly more involved in personal care, assessed by the MACA‐YC18, and exhibited significantly higher emotional symptoms and total difficulties scores on the SDQ than non‐young carers. Conclusion These findings highlight the need for targeted support for young carers—particularly those caring for family members with mental health problems—within schools and the broader community.